Lets read together old mother hubbard: early reading - Bryant-Mole, Karen (Ladybird Books Ltd Devon, 1997)
"Old Mother Hubbard" is a classic nursery rhyme that tells the whimsical story of a kind old woman who goes to her cupboard to fetch her dog a bone. However, she finds the cupboard bare, leading to a series of humorous and unexpected events. Each verse presents a new scenario, showcasing Old Mother Hubbard's efforts to care for her beloved dog, despite the challenges she faces. The playful rhymes and rhythmic structure make it a delightful read for young children, introducing them to the joy of storytelling and the fun of imaginative adventures.